Islamic Religious Education Through Social Media in Reducing Patriarchal Culture - Abdullah, Aji; Vambudi, Viky Nur; Ganapathy, Malini (Suhuf: International Journal of Islamic Studies, 2026)
Background: Patriarchal culture remains a social phenomenon that influences gender relations in society, including in educational practices and religious understanding. Objective: This study aims to analyze the role of Islamic religious education through the utilization of social media as an effort to reduce patriarchal culture. Methodology: This study used a Systematic Literature Review with PRISMA, selecting 23 relevant studies from 2021–2025, and analyzed them with thematic coding to identify key findings on social media in Islamic Religious Education and patriarchal culture. Result: The results of the study indicate that patriarchal culture is largely influenced by social constructions and non-contextual interpretations of religious teachings. Islamic religious education delivered through social media has significant potential to foster a more inclusive religious understanding that emphasizes the values of justice and gender equality. Conclusion: Through communicative and contextual digital da’wah approaches, social media can serve as an effective educational medium to enhance public awareness of equitable gender relations from an Islamic perspective. Implications: This study implies the importance of developing inclusive digital da’wah strategies by educators and preachers, as well as the need for further research based on empirical approaches to gain a deeper understanding of digital da’wah practices.